Systematic review of African-American women’s identity struggle in American drama - Alsanafi, Ismael Hasan; Mohd Noor, S.N.F. (Universiti of Zulia, 2018)
This article carries out a review of the literatures of the related materials that approach the main area of my study which is African American women's lack of identity. As a result, black women in America experience various kinds of oppressions throughout their live but this issue has been changed in the second half of 20th century because of many social, political and literary movements. In conclusion, postmodern drama and Civil Right Movement provide the fertile background for many playwrights at that time to promote the development of a political, literary and social agendas.